Technologies Supporting Pandemic Restrictions in the Hospitality Industry, Hitherto Experiences and Outlook - URBAN, Wieslaw; ŁUKASZEWICZ, Krzysztof (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.12.1(49).17, 2021)
The circumstances of the Covid-19 pandemic established new conditions for the hospitality industry, pandemic restrictions precluded full provision of leisure services. The study aims to identify technological concepts that could noticeably support the industry in dealing with pandemic restrictions while allowing guests take advantage of hospitality services. This is a conceptual study based on comprehensive review of the scientific literature and secondary sources, supported by the creative methodology. Twelve technological device concepts are elaborated, then evaluated, how they support pandemic-related restrictions and affect customer experience. Proposed concepts are aiming at the state of the art and beyond. The study mainly contributes with technological conceptualizations conceivably inspiring further developments favorable to the hospitality industry, particularly in pandemic time. The study presents a value co-creation analysis of the device concepts, several conclusions referring to the implementation of technologies in the hospitality industry are drawn up. One of the conclusions is that the current pandemic situation brings an opportunity to move toward the Industry 4.0 transformation. The study concerns a wider problem of technological changes than just pandemic restrictions.